Narrowing the 'Digital Divide': The Role of Complementarities Between Fixed and Mobile Data in South Africa - Ryan Hawthorne; Lukasz Grzybowski (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study substitution between fixed and mobile broadband services in South Africa using survey data on 134,000 individuals between 2009 and 2014. In our discrete-choice model, individuals choose fixed or mobile voice and data services in a framework that allows them to be substitutes or complements. We find that voice services are complements on average but data services are substitutes. However, many consumers see data services as complements. Our results show that having a computer and access to an internet connection at work or school are more important than reducing mobile data prices by 10% in driving broadband penetration.
Keywords: L13; L43; L96; 330; fixed-to-mobile substitution; mobile broadband; fixed broadband